2019
DOI: 10.1002/jcla.22903
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1RA suppresses esophageal cancer cell growth by blocking IL‐1α

Abstract: BackgroundInterleukin‐1 promotes tumor angiogenesis through VEGF production. The interleukin‐1 receptor antagonist can suppress tumors by blocking this effect.MethodsImmunohistochemistry, WB, and gene sequencing were used to analyze the expression of IL‐1RA in esophageal cancer patients. WB was used to detect the expression of IL‐1RA and interleukin‐1α in esophageal cancer cells. Stable ESCC cell models overexpressing the IL‐1RA were constructed. Their cell functions were tested, and their effects on VEGF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…IL-1 is involved in promoting angiogenesis through the production of vascular endothelial growth factor (VEGF) [ 73 ]. The downregulated expression of IL-1 receptor antagonist (IL-1RA) in EC is associated with tumor progression and poor survival [ 74 ]. Overexpression of IL-1RA in IL-1α expressing KYSE410 EC cells decreased proliferation and reduced expression of VEGF-A [ 74 ].…”
Section: Cytokine/chemokine Expression In Esophageal Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…IL-1 is involved in promoting angiogenesis through the production of vascular endothelial growth factor (VEGF) [ 73 ]. The downregulated expression of IL-1 receptor antagonist (IL-1RA) in EC is associated with tumor progression and poor survival [ 74 ]. Overexpression of IL-1RA in IL-1α expressing KYSE410 EC cells decreased proliferation and reduced expression of VEGF-A [ 74 ].…”
Section: Cytokine/chemokine Expression In Esophageal Cancermentioning
confidence: 99%
“…The downregulated expression of IL-1 receptor antagonist (IL-1RA) in EC is associated with tumor progression and poor survival [ 74 ]. Overexpression of IL-1RA in IL-1α expressing KYSE410 EC cells decreased proliferation and reduced expression of VEGF-A [ 74 ]. On the contrary, no effect of IL-1RA overexpression was observed in EC9706 cells (low IL-1α expression) proliferation and VEGF-A expression [ 74 ].…”
Section: Cytokine/chemokine Expression In Esophageal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found that IL-1ra was a competitive inhibitor of IL-1(α/β) [49] and was neuroprotective in the mice that had a stroke [50]. IL-1ra could also suppress the growth of esophageal cancer cells by blocking IL-1α [51]. In this article, IL-1ra could play a crucial role because it was clearly related with MDSCs and CD68 + CD163 + M2-like macrophages in NSCLC patients in RT, which deserved deep investigations in the following experiments.…”
Section: Discussionmentioning
confidence: 99%